Premarital Counseling as an Effort to Prevent and Anticipate Divorce in Early Marriages from an Islamic View - Silvan Khowiyunanto; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Premarital education refers to knowledge and skill-based training that equips couples with information on how to maintain and improve their relationship after marriage, particularly for couples who marry at a young age. The purpose of this study is to assess the effectiveness of premarital counseling as a solution to the issue of early marriage. This qualitative research employs a case control design with focused interviews and data collection methods including literature review and observation. The findings indicate that 10 couples who had early marriages, with at least a high school education, did so due to pregnancy before marriage. Counseling was provided to the prospective bride and groom just before the wedding to strengthen their mindset and thoughts. The outcome of the study indicates that premarital counseling is highly impactful for prospective early brides as it can help them become better and wiser individuals. Also, proper parental guidance and education are necessary to prevent early marriage from becoming a cultural norm, especially in Ponorogo.